Sleep deprivation disturbed regional brain activity in healthy subjects: evidence from a functional magnetic resonance-imaging study - Wang L (Dove Medical Press, 2016)
Li Wang, Yin Chen, Ying Yao, Yu Pan, Yi Sun Department of Neurology, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China Objective: The aim of this study was to use amplitude of low-frequency fluctuation (ALFF) to explore regional brain activities in healthy subjects after sleep deprivation (SD).Materials and methods: A total of 16 healthy subjects (eight females, eight males) underwent the session twice: once was after normal sleep (NS), and the other was after SD. ALFF was used to assess local brain features. The mean ALFF-signal values of the different brain areas were evaluated to investigate relationships with clinical features and were analyzed with a receiver-operating characteristic curve.Results: Compared with NS subjects, SD subjects showed a lower response-accuracy rate, longer response time, and higher lapse rate. Compared with NS subjects, SD subjects showed higher ALFF area in the right cuneus and lower ALFF area in the right lentiform nucleus, right claustrum, left dorsolateral prefrontal cortex, and left inferior parietal cortex. ALFF differences in regional brain areas showed high sensitivity and specificity. In the SD group, mean ALFF of the right claustrum showed a significant positive correlation with accuracy rate (r=0.687, P=0.013) and a negative correlation with lapse rate (r=-0.706, P=0.01). Mean ALFF of the dorsolateral prefrontal cortex showed a significant positive correlation with response time (r=0.675, P=0.016).Conclusion: SD disturbed the regional brain activity of the default-mode network, its anticorrelated “task-positive” network, and the advanced cognitive function brain areas. Keywords: sleep deprivation, amplitude of low-frequency fluctuation, default-mode network, functional magnetic resonance imaging